Corporate ethical governance and accountability: Malaysian evidence of self-regulating ethical culture / Norazamina Mohamed - Mohamed, Norazamina (Institute of Graduate Studies, UiTM, 2014)
Technology advances, competitive rivals and new innovation have changed the business world. What is not changed is the “profit-oriented” mind. Initially, it was a small scale of “profit-oriented” but then it evolves to immense scale of “profitoriented” as to achieve as much as possible high financial return. Evidences of businesses collapse indicate the business world is full with “greedy” and “corrupted” businessmen and practitioners. Therefore, it is recommended for the companies to embark on Corporate Ethical Governance and Accountability and to follow Applied Corporate Governance that view corporate governance not only on the aspect of structuring, operating and controlling but also with the purpose to achieve culture based on sound business ethics by concerning all stakeholders and by complying to all related regulations. The companies can carry out the utmost “best practices” of good corporate citizen through ethical culture. The main purposes of this study are to investigate the existence and practices of ethical culture dimensions and company”s spirituality in Malaysian Public Listed Companies and to examine their relationships with employees” ethical behaviour. The ethical leadership, ethical guidelines in COCC/TACOS/ EH and stakeholder balance are companies” self-regulating dimensions of ethical culture. In addition, a new variable, company”s spirituality is incorporated to stimulate the company”s culture. Briefly these dimensions describe leaders with role model, good relationship and moral characteristics, documented ethical guidelines as a guidance of expected behaviour and stakeholders considerations in all aspects of business dealings. While company”s spirituality is the intrinsic and extrinsic values held by the company. In achieving the objectives, exploratory design method with instrument development model is applied to explore and to generalize these dimensions.